Camp Life: The Queer History of Manhood in the Civilian Conservation Corps, 1933-1937 - Johnson, Colin R. (American Studies, 2007)
Between 1933 and 1942 hundreds of thousands of young American men sought relief from the poverty and hopelessness of the Great Depression by joining FDR’s Emergency Work Relief program, otherwise known as the Civilian Conservation Corps. Although the Corps attracted men from both town and country, the vast majority of work camps to which It sent enrollees were located near small towns or in remote rural areas far from US urban centers. This essay explores the homosocial world of these camps paying particularly close attention to the traditions of gender-bending drag performance and homoerotic innuendo that grew up within them. Following the invitation of Martin Bauml Duberman, who first suggested in 1981 that the CCC might prove to be a worthy subject of inquiry for historians of the gay past, the essay argues that in the organization’s early years especially camp life was, in fact, a camp life—one in which the very meaning of American manhood was constantly being challenged, contested and reworked in ways that bear a striking resemblance to the sometimes coded, sometimes openly flamboyant techniques of sociability typically associated with urban sexual subcultures during this period. As such, it makes a claim for the CCC’s importance as a crucial point of historical connection between the proto-gay subcultures that flourished in American cities during the early twentieth century and the homosexual subculture that arose in another federal entity—the US military—during the Second War World.